The State of Point of Care Ultrasound Certification in South Africa. Why are so Few Providers Completing the Certification Process - Lemke, Franz Gustav (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2014.